Analysis of The Impact of Sedimentation Dredging on Headloss Repair & Operating Patterns of CWP (Circulating Water Pump) PLTU Lontar - Iwa Garniwa; Muhammad Pinandhito Adi Dharma (Sekolah Tinggi Teknik PLN, 2022)
The PLTU Lontar Extension Project (1x315 MW) is a national strategic project being built by PT. PLN (Persero). The project stage is currently in the commissioning phase but is hampered by indications of sedimentation occurring at the intake mouth area of ​​the Circulating Water System. There are indications of sedimentation at the intake mouth due to the high head loss between the intake mouth and the upstream box culvert which has an impact on inhibiting the flow of seawater entering the Lontar PLTU intake canal. The existence of obstacles to the flow of sea water has resulted in insufficient cooling water flow for the needs of 8 Circulating Water Pump (CWP) pumps, namely 6 CWP for 3 units of PLTU Existing and 2 CWP for 1 unit of PLTU Extension. The sea bed level on the side of the intake mouth according to the basic design is -4.5 m but after the survey (bathymetry, topography, floating sediment, currents, tides) the actual condition is currently at a depth of -0.9 m. As one solution, the dredging method is taken to restore conditions according to the basic design. To find out if there is an improvement in headloss, a simulation is carried out using the Hec-ras 2D application. After the simulation, it was found that the headloss/compression loss significantly improved in the hydraulic simulation with a flow rate of 42 m3/s at 6 pumps running, before dredging 30 cm and after dredging to 18 cm and also with a flowrate of 60 m3/s at 8 pumps running. , before dredging 55 cm and after dredging to 21 cm at the right position upstream of the box culvert. This headloss condition is predicted to propagate downstream to the forebay and CWP pump pits, so that dredging in this area is simulated to increase the performance of the Lontar PLTU circulating water intake so that 8 CWPs can operate together continuously.